2003
DOI: 10.1079/bjn2003886
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body fluxes and partitioning of amino acids to the mammary gland of cows fed fresh pasture at two levels of intake during early lactation

Abstract: The utilisation of essential amino acids (EAA) by the mammary gland of lactating dairy cows fed fresh forages was studied to provide basic information useful in designing strategies to increase the production of milk protein from pasture-fed dairy cows. The relationship between the flux of EAA in the whole body and their uptake by the mammary gland was determined in four cows in early lactation (length of time in milk 44 (SD 14·5) d) producing 21 (SD 4·0) kg milk/d. The cows were maintained in metabolism stall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Higher mammary plasma fl ow and peripheral BCAA concentration could explain the elevated mammary uptake in control ewes (CT active). This agrees with results showing that BCAA are taken up by the bovine mammary gland not only for milk protein synthesis but also for oxidation or synthesis of metabolites important for mammary function (Pacheco et al, 2003).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Higher mammary plasma fl ow and peripheral BCAA concentration could explain the elevated mammary uptake in control ewes (CT active). This agrees with results showing that BCAA are taken up by the bovine mammary gland not only for milk protein synthesis but also for oxidation or synthesis of metabolites important for mammary function (Pacheco et al, 2003).…”
Section: Discussionsupporting
confidence: 82%
“…Mammary blood fl ow was measured continuously during this period. Plasma was obtained from blood samples collected from the blood vessels mentioned previously for measuring AA (Pacheco et al, 2003) and pAH concentration (Huntington et al, 1989). One control ewe died for reasons not related to the treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…High ambient temperatures are well known to reduce milk protein production in lactating dairy cows (Brash et al 2001). Nitrogen utilization for milk production by lactating dairy cows declines under high ambient temperature and feed restriction (Terada & Shioya 1998;Pacheco et al 2003). Our previous report (Kamiya et al 2005) also indicated that high ambient temperature, feed restriction, and high ambient temperature itself reduced the nitrogen utilization for milk production by lactating dairy cows.…”
Section: Introductionmentioning
confidence: 93%
“…2001). Nitrogen utilization for milk production by lactating dairy cows declines under high ambient temperature and feed restriction (Terada & Shioya 1998; Pacheco et al . 2003).…”
Section: Introductionmentioning
confidence: 99%